ON SOLVABILITY OF AN INFINITE NONLINEAR SYSTEM OF ALGEBRAIC EQUATIONS WITH TEOPLITZ–HANKEL MATRICES - Khachatryan, Kh.A.; Avetisyan, M.H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
In the present paper a special class of infinite nonlinear system of algebraic equations with Teoplitz–Hankel matrices is studied. Above mentioned class of equations has direct applications in radiative transfer theory. Existence componentwise positive solutions for the system in space l1 are proved and some examples for mentioned equations, representing separate interest are given.
Keywords: positive solution, Teoplitz–Hankel type matrices, iteration, limit of solution